New insight in endocrine-related adverse events associated to immune checkpoint blockade. Issue 1 (January 2020) - Elia, Giusy; Ferrari, Silvia Martina; Galdiero, Maria Rosaria; Ragusa, Francesca; Paparo, Sabrina Rosaria; Ruffilli, Ilaria; Varricchi, Gilda; Fallahi, Poupak; Antonelli, Alessandro
Abstract : Anticancer immunotherapy, in the form of immune checkpoint inhibition, is a paradigm shift that has transformed the care of patients with different types of solid and hematologic cancers. The most notable improvements have been seen in patients with melanoma, non-small-cell lung, bladder, renal, cervical, urotherial, and colorectal cancers, Merkel cell carcinoma, and Hodgkin lymphoma. Monoclonal antibodies (mAbs) targeting immune checkpoints (i.e., anti-CTLA: ipilimumab; anti-PD-1: nivolumab, pembrolizumab; anti-PD-L1: durvalumab, atezolizumab, avelumab) unleash the immune system against tumor cells targeting mainly T cells. Treatment with immune checkpoint inhibitors (ICIs) is associated with a variety of diverse and distinct immune-related adverse events (irAEs), reflecting the mechanistic underpinning of each target (i.e., CTLA-4, and PD-1/PD-L1 network). The most frequent endocrine irAEs associated with anti-PD-1 mAb treatment are thyroid dysfunctions, whereas hypophysitis is mostly linked to anti-CTLA-4 treatment. Type 1 diabetes mellitus and adrenalitis are rare irAEs. Combination therapy (anti-CTLA-4 plus anti-PD-1/PD-L1) can be associated with an increased risk and prevalence of endocrine irAEs. In this paper we discuss the pathophysiological and clinical aspects of irAEs with specific emphasis on endocrine irAEs associated with ICIs. With a growing number of patients treated with ICIs, a tight collaboration among oncologists, endocrinologists and immunologists appears necessary when the circumstances are more challenging and for better management of severe endocrine irAEs. Further investigations are urgently needed to better understand the mechanisms by which different ICIs can induce a variety of endocrine irAEs.